Summary of The Value Accounting of Ecological Products - Shi, Yanlong (International Journal of Management and Education in Human Development, 2023)
The value accounting of ecological products is a concrete action to implement the harmonious coexistence between man and nature, and is an important technical basis to promote the realization of the value of ecological products. This paper systematically sorts out the background of the value of ecological products, the definition, methods and existing problems of the value accounting of ecological products at home and abroad, and puts forward the following suggestions to strengthen the accounting of theoretical methods and the value of ecological products, and promote the value accounting system of ecological products. At the same time, in the future, we should actively improve the basic theoretical framework of ecological product value accounting, and improve the basic theoretical framework of ecological product value accounting.